Democracy promotion, post-truth politics and the practices of political expertise. Issue 1 (2nd January 2022) - Christensen, Michael
Abstract: Disinformation and other forms of post-truth politics are clearly a threat to global democracy. One way to better understand this post-truth moment is to re-examine the recent history of how political actors have tried to build or defend democratic institutions. This article turns to the field of international democracy promotion to examine the problem of legitimacy and trust in democratic institutions. While it has evolved from its late Cold War roots in pro-democracy propaganda campaigns, democracy promotion has increasingly become a field of expert knowledge aimed at professionalizing or improving the capacity of democratic institutions. This research follows the recent practice turn in IR theory to examine how expert knowledge is enacted through everyday organisational practices and argues that the recent rise of post-truth politics was not coincidental to the professionalisation of the field. Through interviews, ethnographic research, and document analysis of North American democracy promotion organisations, the following presents an analysis of contemporary democracy promotion as a set of practices emerging out of a global backlash against democracy that started in the early 2000s. The findings of this research suggest that performances of expertise in this field tend to be de-politicised, indeterminate, and narrowly focused on institutional legitimacy.